An outstanding NiFe/NF oxygen evolution reaction boosted by the hydroxyl oxides. (20th February 2023) - Chen, Yuehui; Zeng, Xianhui; Meyer, Quentin; Zhao, Chuan; He, Zhenjiang; Wu, Feixiang; Tang, Haolin; Cheng, Yi
Abstract: NiFe-based and NiCo-based catalysts are promising alternatives to noble-metal catalysts for the oxygen evolution reaction (OER) due to their excellent catalytic activity, low cost and abundant resources. However, the active sites nature, along with the pathway to achieve the highest electroactivity, remains unclear. Herein, we use nickel foam (NF) as carrier and prepared NiFe/NF and NiCo/NF catalysts with excellent OER catalytic activity and stability by electrodeposition and calcine them either in Air or H2 /Ar after deposition. In 1 M KOH media, the overpotential of NiFe/NF at 50 mA cm −2 is only 182 mV, which one of the lowest for OER reported to date. By analyzing the influence of the morphology, structure and surface chemical states caused by calcination on performances, we found that the ratio of hydroxide/hydroxyl oxide to lattice oxygen heavily impacts the OER with higher hydroxide/hydroxyl oxide to lattice oxygen ratio achieving the highest catalytic activity. This work significantly furthers the understanding of the OER mechanism on the surface of NiFe and NiCo catalysts and provides insights for regulating NiFe and NiCo catalysts to achieve higher OER performance. Graphical abstract: Image, graphical abstract